Mechanical aptitude and spatial relations tests - Wiesen, Joel P. (Joel Peter) (Kaplan North America, LLC, d/b/a Barron's Educational Series, 2023)
Private employers and public agencies use various mechanical aptitude tests to screen applicants for jobs that range from mechanics and skilled trades apprentices to aerospace engineers and firefighters. These tests often differ in detail but measure similar abilities. This manual presents 18 typical tests that gauge an individual's mechanical aptitude and spatial ability, with all questions answered and explained. The author also advises on ways to improve mechanical comprehension, gives test-taking tips, and explains how pulleys, levers, and other simple machines work. The book is filled with diagrams and illustrations.